Republic of Latvia : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Latvia. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that Latvia's government revenues overperformed in 2017, buoyed by strong economic activity and wage growth. Nonetheless, the 2017 general government structural balance recorded a deficit of 0.8 percent of GDP, which resulted in a positive fiscal impulse rendering fiscal policy procyclical. Despite the suspension of activities of Latvia's third largest bank on money laundering concerns, the banking system remains well capitalized and liquid, with capital-to-risk-weighted assets of 22.4 percent and liquid assets exceeding 80 percent of short-term liabilities at end-March 2018. Deleveraging of both households and nonfinancial corporations continued, with household debt to income now at half of its pre-crisis levels.